2018
DOI: 10.1007/s11469-018-9941-5
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Emotional Trauma and Cyberbullying Perpetration Among Emerging Adults: A Multiple Mediation Model of the Role of Problematic Social Media Use and Psychopathology

Abstract: Research suggests that a small minority of social media users experience problems as a result of their online use. The purpose of the present study was to examine the association of cyberbullying perpetration and problematic social media use with childhood emotional trauma, Cluster B (narcissistic, histrionic, antisocial, and borderline) personality traits, dissociative experiences (DEs), depression, and self-esteem in a nonclinical undergraduate sample. A total of 344 university students volunteered to comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
28
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 109 publications
(110 reference statements)
6
28
0
2
Order By: Relevance
“…As expected (H1), CEA was directly associated with CBP. This result is consistent with the previous empirical literature which has reported direct associations of emotional and psychological maltreatment with CBP (Kircaburun et al 2018b;Lyu and Zhang 2017). Furthermore, this result can be explained by the theoretical assumptions that posit individuals will observe others' behaviors and mimic them in similar situations (Bandura 2002).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…As expected (H1), CEA was directly associated with CBP. This result is consistent with the previous empirical literature which has reported direct associations of emotional and psychological maltreatment with CBP (Kircaburun et al 2018b;Lyu and Zhang 2017). Furthermore, this result can be explained by the theoretical assumptions that posit individuals will observe others' behaviors and mimic them in similar situations (Bandura 2002).…”
Section: Discussionsupporting
confidence: 93%
“…Getting victimized by emotional abuse as a child may result with impairments in one's moral justification, reasoning, and standards (Bandura 1999) in which moral values may be a particularly important preventive factor for reducing CBP because-contrary to the preventive laws for traditional bullying (Patchin and Hinduja 2018)-disincentive punishment that may stop individuals bullying others in online contexts is inadequate in most jurisdictions (Hinduja and Patchin 2014). Furthermore, a recent empirical study suggested that emotional maltreatment can be associated with higher CBP among university students and that self-report personality disorders may partially mediate this relationship (Kircaburun et al 2018b). Another study indicated that psychological maltreatment was directly and indirectly associated with CBP via moral disengagement among college students (Lyu and Zhang 2017).…”
Section: Childhood Emotional Abuse and Cyberbullying Perpetrationmentioning
confidence: 99%
See 1 more Smart Citation
“…IGD could be impacted by a lot of other variables. Internet-related disorders should be considered within an integrative theoretical framework, covering the aspects of biopsychological factors, social factors, psychopathological factors, personality traits and other specific motivations (Brand, Young, Laier, Wolfling, & Potenza, 2016;Kircaburun, Demetrovics, Kir aly, & Griffiths, 2018). We recommended that future studies use comprehensive measurements covering multiple factors.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that, when controlling for gender, Big Five personality traits, and sleep quality, eveningness was a predictor of CBP (Kircaburun & Tosuntaş, 2018). Given that negative factors such as emotional instability, impulsivity, and psychopathology are important determinants of CBP (Erreygers et al, 2016;Kircaburun et al, 2018a;Kircaburun & Tosuntaş, 2018), the evening chronotype may be expected to directly associate with higher CBP.…”
Section: Chronotype and Cyberbullying Perpetrationmentioning
confidence: 99%